Developing Funnel-Based Visual Media for Teaching Integer Addition to Third Grade Elementary Students - Salwa Arifiani, Fathia; Jayanti; Suryani, Ida; Lachlan, Nicholas (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This research focuses on the development of visual learning media based on counting funnels in mathematics lessons to teach integer addition to third-grade elementary school students using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study originated from observations at SD Negeri 89 Palembang, which revealed low student engagement in mathematics learning due to the use of conventional and less attractive media that made it difficult for students to understand mathematical concepts concretely. Therefore, innovative learning media suited to the characteristics and learning needs of elementary students were needed. The purpose of this research was to determine the validity, practicality, and effectiveness of the counting funnel media in supporting the learning process. The research was conducted through the ADDIE stages, including analysis of learning needs, media design, development through expert validation, classroom implementation, and final evaluation. The results showed that the media was declared valid based on expert assessments, practical in classroom application, and effective in improving students’ understanding of integer addition. The findings confirmed that the counting funnel media is feasible and beneficial as a learning aid. The implications indicate that this visual media can serve as an alternative solution to enhance conceptual understanding, motivation, and student engagement. Overall, this study concludes that counting funnel media effectively supports meaningful and enjoyable mathematics learning for elementary school students.